(untitled) (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2026)
This studyiaims to evaluate the influence of perceived ease, benefits, trust, and risk on publiciinterest in using the BRImo m-banking applicationiin Semarang City. The approach used is quantitative, with the target of the study being BRImo users domiciled in Semarang. The samplingitechnique was carried out non-probabilityiwith the purposive samplingimethod, namely selecting 110 respondents who had actively used BRImo for at least one year. Dataianalysis was carried out through multiple linear regressioniusing SPSS version 26 software. Basedion theiresultsiof the partial test (t test), perceived ease did not show a significantieffect oniinterest in using BRImo (t count <t table, 1.227 <1.982). Onithe other hand, perceived benefits had a positive and significant effect on interest in use (t count> t table, 3.431> 1.982), as well as the trust variable (ticount> t table, 3.442> 1.982). On the other hand, risk perception does not have a significant effect (t count < t table, 0.262 < 1.982). Theiresultsiof the simultaneous testi(F test) showithat all independentivariables together influence the interest in using BRImo (F count > F table, 28.224 > 2.46). The resultsiof this study areiexpected to provide practical contributions toibankingiin improving digital services, help users understand the factors that drive interest in using BRImo, and become a scientific reference in the field of digital service marketing research.